The description of Ilokano in the 17th century (Linguistics in Amsterdam, 2014)
The grammar Arte de la lengua ilocana (1627) was written by the Augustinian Francisco López (?–1627) in order to learn the language and to be able to spread the Christian doctrine in the Philippines. It is the first description of this Austronesian language. It is written in Spanish and based on data from an oral corpus and translated texts, mainly doctrines and gospels. It has almost 200 pages divided in two parts: morphology and verbs. There is also the usual license, a poem written by an Ilokano native, an index and an errata sheet. It follows the lead of Antonio de Nebrija’s grammar, because, as the author said, the missionaries had learnt Latin with the help of Nebrija‘s books, so it was easier for them to learn a new language using the usual methods. However, López includes some innovations, because Ilokano is very different from Latin. To sum up, this grammar was very didactic, and so complete and easy to use that any missionary who wanted to learn Ilokano had to study it and could do it quickly because of its graphics and translations.